Zinc-energized dynamic hydrogel accelerates bone regeneration via potentiating the coupling of angiogenesis and osteogenesis - Lv, Nanning; Zhou, Zhangzhe; Hong, Lihui; Li, Hongye; Liu, Mingming; Qian, Zhonglai (Frontiers in Bioengineering and Biotechnology, 2024)
Insufficient initial vascularization plays a pivotal role in the ineffectiveness of bone biomaterials for treating bone defects. Consequently, enhancing the angiogenic properties of bone repair biomaterials holds immense importance in augmenting the efficacy of bone regeneration. In this context, we have successfully engineered a composite hydrogel capable of promoting vascularization in the process of bone regeneration. To achieve this, the researchers first prepared an aminated bioactive glass containing zinc ions (AZnBg), and hyaluronic acid contains aldehyde groups (HA-CHO). The composite hydrogel was formed by combining AZnBg with gelatin methacryloyl (GelMA) and HA-CHO through Schiff base bonding. This composite hydrogel has good biocompatibility. In addition, the composite hydrogel exhibited significant osteoinductive activity, promoting the activity of ALP, the formation of calcium nodules, and the expression of osteogenic genes. Notably, the hydrogel also promoted umbilical vein endothelial cell migration as well as tube formation by releasing zinc ions. The results of in vivo study demonstrated that implantation of the composite hydrogel in the bone defect of the distal femur of rats could effectively stimulate bone generation and the development of new blood vessels, thus accelerating the bone healing process. In conclusion, the combining zinc-containing bioactive glass with hydrogels can effectively promote bone growth and angiogenesis, making it a viable option for the repair of critical-sized bone defects.